2011
DOI: 10.1128/cvi.00036-11
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity against Experimental Pulmonary Cryptococcosis in T Cell-Depleted Mice

Abstract: Individuals with defects in T cell-mediated immunity (CMI) are highly susceptible to infection with Cryptococcus neoformans. The purpose of these studies was to determine if protection against experimental pulmonary cryptococcosis can be generated in T cell-deficient hosts. BALB/c mice were depleted of CD4 ؉ and/or CD8 ؉ T cells or given an isotype control antibody prior to vaccination with a C. neoformans strain, designated H99␥, previously shown to induce protection against C. neoformans infection in immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 40 publications
5
59
0
Order By: Relevance
“…A 2011 study demonstrated that when immunocompetent mice were immunized with an interferon-gamma-producing strain of C. neoformans (H99γ) and subsequently rendered CD4 and CD8 T cell deficient, the vaccine conferred protection for up to 100 days postimmunization [68]. Separately, a recent report by Rella et al [69] describes a nonpathogenic sterylglucoside mutant strain of C. neoformans that conferred complete protection against lethal doses of both C. neoformans and C. gattii in mice.…”
Section: Fungal: Cryptococcusmentioning
confidence: 99%
“…A 2011 study demonstrated that when immunocompetent mice were immunized with an interferon-gamma-producing strain of C. neoformans (H99γ) and subsequently rendered CD4 and CD8 T cell deficient, the vaccine conferred protection for up to 100 days postimmunization [68]. Separately, a recent report by Rella et al [69] describes a nonpathogenic sterylglucoside mutant strain of C. neoformans that conferred complete protection against lethal doses of both C. neoformans and C. gattii in mice.…”
Section: Fungal: Cryptococcusmentioning
confidence: 99%
“…Pulmonary C. neoformans infections were initiated by nasal inhalation as described previously (11,12,22). Mice were anesthetized with 2% isoflurane using a rodent anesthesia device (Eagle Eye Anesthesia, Jacksonville, FL) and were then given a yeast inoculum of 1 ϫ 10 4 CFU of C. neoformans strain H99 or H99␥ in 50 l of sterile PBS pipetted directly into the nostril.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental murine studies using a C. neoformans strain engineered to express gamma interferon (IFN-␥), designated H99␥, have shown that pulmonary infection with H99␥ results in the induction of Th1-type cytokine responses in the lung, lymphocyte recruitment, reduced fungal burdens, and complete protection against an otherwise lethal challenge with C. neoformans (11)(12)(13). Cell-mediated immunity (CMI) by Th1-type CD4 ϩ T cells is important for the induction of protective immunity against C. neoformans (12,14).…”
mentioning
confidence: 99%
“…In a more recent study, depletion of CD4 þ or CD8 þ T cells during the immunization phase ( primary infection with H99g) or secondary lethal infection protected 100% of mice from mortality. However, when both CD4 þ and CD8 þ T cells were depleted during immunization with H99g or secondary infection, mortality reached 100% (Wozniak et al 2011). Although the H99g strain vaccine could not be used in humans, it does serve as a proof of concept for live vaccination strategies, whereby pathogens are genetically engineered to produce cytokines that enhance host-protective responses.…”
Section: Fungal Vaccines and Immunotherapeuticsmentioning
confidence: 99%